Atlas of Postsurgical Neuroradiology : Imaging of the Brain, Spine, Head, and Neck - Ginat, Daniel Thomas; Westesson, Per-Lennart A. (Springer International Publishing : Imprint: Springer, 2017)
This book, now in a revised and updated second edition, remains a unique reference on postoperative neuroimaging. It is designed as a guide that will familiarize the reader with the radiological features of various types of surgical procedures, implanted hardware, and potential complications. Specific topics covered include imaging after facial cosmetic surgery; orbital and oculoplastic surgery; sinus surgery; scalp and cranial surgery; brain tumor treatment; psychosurgery, neurodegenerative surgery, and epilepsy surgery; skull base surgery, including transsphenoidal resection; temporal bone surgery, including various ossicular prostheses; orthognathic surgery; head and neck oncologic surgery, including neck dissection and flap reconstruction; CSF diversion procedures and devices; spine surgery; and vascular and endovascular neurosurgery. The book is written by experts in the field and contains an abundance of high-quality images and concise descriptions. It will be of value for neuroradiologists, neurosurgeons, and otolaryngologists wishing to deepen their knowledge of the imaging correlates of postsurgical findings and to improve their ability to interpret images correctly.
Keywords: Medicine.; Neuroradiology.; Neurosurgery.; Otolaryngologic surgery.; elektronické knihy; electronic books